Recovery of Sodium Dichromate in Process of Chlorate Production - Zhou, Junbo; Pan, Sujuan; Guo, Shufen; Gao, Liping (Asian Journal of Chemistry, 2014)
A large amount of sludge was generated for removal sulfate radical using chemical precipitation during sodium chlorate industry. The sludge also contains sodium dichromate, Cr(VI) in it pollutes the environment when the sludge is discarded without treatment. Recently the treatment of mother liquor in sodium chlorate industry gains much interest. The use of ion exchange resin and nanofiltration membrane device integrated treatment of sodium chlorate industry crystallization mother liquor was presented. The recovery rate of sodium dichromate can reach 98 % and sodium sulfate in the crystallization mother liquor is less than 3 g/L after treatment, reaching the recycling requirement.